Comparative analysis of the seed microbiome in four major oilseed crops (rapeseed, sunflower, soybean, sesame) reveals host-specific assembly and potential application of seed core microbes - Yao, Yao; Zhao, Lelin; Zhang, Yun; Duan, Ailing; Yang, Yuanxue; Wang, Aiyu; Xue, Chao; Zhang, Jianhua; Zhao, Ming (Frontiers in Plant Science, 2026)
The oilseeds are abundant in oils and proteins, and the production of high-quality oilseeds represents a major objective in modern agriculture. However, oilseed production is constrained by biotic and abiotic stresses, resulting in the decreasing in yield and quality. The seed microbiome has been recognized as a critical determinant of plant health. However, its composition and functional roles in various oilseed crops remains poorly explored. In this study, we utilized 16S rRNA gene amplicon sequencing to compare the bacterial component of seed microbiome and predict their metabolic potential in four oil crops (rapeseed, sunflower, sesame, soybean). Our results revealed that the oilseed harbored high diverse of microbes, and the assembly of microbial community was not random but driven by species and cultivar. From the perspective of microbial functions, the lipid metabolism and other secondary metabolites of seed microbes were associated with corresponding metabolic processes in seeds, such as glucosinolate and linoleic acid, reflecting the functional connection between seed metabolites and seed microbes. Furthermore, the core microbiome was obtained among four oilseed groups, consisting of 18 bacterial amplicon sequence variants (ASVs), including putative plant-beneficial resources, such as Sphingomonas. Notably, strain SE-S32 (Sphingomonas endophytica) isolated from rapeseed seed, one of the core microbes, could improve the resistance of various crops, indicating that seed core microbes could serve as a microbial inoculant among multiple crops. These results provide new insights into the correlation between seed microbiome and seed metabolites, establishing a theoretical foundation for developing microbial strategies to improve oilseed quality and plant health.